E. coli Surface Properties Differ between Stream Water and Sediment Environments - Liang, Xiao; Liao, Chunyu; Thompson, Michael L.; Soupir, Michelle L.; Jarboe, Laura R.; Dixon, Philip M. (Frontiers in Microbiology, 2016)
The importance of E. coli as an indicator organism in fresh water has led to numerous studies focusing on cell properties and transport behavior. However, previous studies have been unable to assess if differences in E. coli cell surface properties and genomic variation are associated with different environmental habitats. In this study, we investigated the variation in characteristics of E. coli obtained from stream water and stream bottom sediments. Cell properties were measured for 77 genomically different E. coli strains (44 strains isolated from sediments and 33 strains isolated from water) under common stream conditions in the Upper Midwestern United States: pH 8.0, ionic strength 10 mM and 22°C. Measured cell properties include hydrophobicity, zeta potential, net charge, total acidity, and extracellular polymeric substance (EPS) composition. Our results indicate that stream sediment E. coli had significantly greater hydrophobicity, greater EPS protein content and EPS sugar content, less negative net charge, and higher point of zero charge than stream water E. coli. A significant positive correlation was observed between hydrophobicity and EPS protein for stream sediment E. coli but not for stream water E. coli. Additionally, E. coli surviving in the same habitat tended to have significantly larger (GTG)5 genome similarity. After accounting for the intrinsic impact from the genome, environmental habitat was determined to be a factor influencing some cell surface properties, such as hydrophobicity. The diversity of cell properties and its resulting impact on particle interactions should be considered for environmental fate and transport modeling of aquatic indicator organisms such as E. coli.